Novos diterpenos isolados das raízes de Xylopia langsdorffiana St-Hil & Tul. (Annonaceae) - Santos, Paula Ferreira dos (2011)
Xylopia langsdorffiana (Annonaceae), popularly known pimenteira-da-terra, is a tree that can reach 5-7 m of height. Phytochemical studies reported the presence of alkaloids and terpenoids type trachylobane, atisane, labdane and kaurane of the fruits, stem and leaves. In this work we report the isolation and structural elucidation of terpenes isolated from roots of X. langsdorffiana. Chromatographic analysis of the crude ethanolic extract of the roots allowed the isolation of seven diterpenes: ent-7β-acetoxytrachyloban-18-oic acid, reported in the species, ent-trachyloban-18-oic acid, ent-kauran-16β-ol, ent-kaur-16-en-19-oic acid and ent-kaur-16-en-19-ol, first reported in the species, ent-atisan-7α-acetoxy-16α-ol and entatisan- 7-oxo-16α-ol first reported in the literature, and trivially named Acetato de Xylodiol and Xylopinona. The chemical constituents were identified by date analysis obtained for spectroscopic methods as Infrared, high and low resolution Mass Spectrometry obtained by ESI (HR-ESI-MS), 1H, 13C Nuclear Magnetic Resonance unidimensional and bidimensional techniques (COSY, NOESY, HMQC e HMBC), and compared with previously reported data. The roots were subjected to essencial oil extraction by hydrodistillation in Clevenger apparatus and characterized in GC-MS, was possible identify 89.9% of the chemical constituents oil. The major constituent is the trans-isolimonene (56.63%) and espathulenol 0.11% that is considered the marker of Xylopia genus. This way, the obtained results contributed with chemotaxonomic knowledge of Annonaceae family, especially Xylopia langsdorffiana.